Barn owls display larger black feather spots in cooler regions of the British Isles. (22nd April 2016) - Roulin, Alexandre; Randin, Christophe F.
Abstract : Although, in many organisms, genotypes are adapted to specific environmental conditions, the identification of the ecological factors explaining patterns of local adaptation is not a trivial task. In relation to the cosmopolitan barn owl ( Tyto alba ), its plumage varies from white to dark pheomelanic and shows a difference in the number and size of black spots located at the tip of ventral feathers. The expression of these traits is strongly heritable and weakly sensitive to variation in body condition. Therefore, if owls located in cold or rainy regions are differently plumaged compared to owls living in warm or dry regions, this may not be a result of climate affecting the expression of plumage traits. Instead, different plumages might be selected under different environmental conditions. We have found that, on the British Isles, comparatively larger spots are present on barn owls found in regions that are cooler in summer. This is similar to the findings of a previous study performed in North America and on continental Europe, raising the possibility that larger‐spotted barn owls better cope in cold temperatures during the rearing period or that they are better adapted to some environmental factors prevailing in cooler summers.